Validation and Feasibility of the Medication Acceptability Questionnaire to Investigate Tablet and Liquid Alendronic Acid with Older Hospital Patients - Sion Scott; Allan Clark; Helen May; Debi Bhattacharya (MDPI AG, 2018)
The effects of formulation characteristics on acceptability are poorly understood. This study evaluated the validity and feasibility of using the Medication Acceptability Questionnaire (MAQ) to investigate factors influencing acceptability of tablet compared with liquid alendronic acid. Written consent was obtained from eligible patients on Older People's Medicine wards. MAQ face and content validity were evaluated through cognitive interviews while internal consistency and criterion validity were investigated by calculating Cronbach's alpha and correlation of MAQ items with visual analogue scale (VAS) responses. MAQ data were obtained from 33 and 25 participants for tablet and liquid formulations respectively. Cognitive interviews indicated MAQ face and content validity. The domains of appearance, efficacy, and tolerability demonstrated adequate internal consistency and suitable refinements were identified for the domains of convenience and taste with Cronbach's alpha <0.7. Significant positive correlations were identified between all MAQ domains and VAS. The liquid trended towards performing better for taste, appearance and tolerability and the tablet for convenience and efficacy. It is feasible to capture patient acceptability of a medication by questionnaire. Interpatient variation in acceptability for two formulations indicates that medication characteristics should be considered during prescribing and medication reviews to match patient preference with the appropriate formulation.